Effect of General Difference in Personality Traits and Attitude among Male and Female Students: A Review (Advances in Applied Biological Research, 2024)
This comprehensive review delves into the intriguing realm of personality traits and attitudes among male and female students. Personality traits signify unique individual qualities, while attitudes reveal the intricate interplay of emotions, beliefs, and cognitive patterns. The spotlight shines on the renowned "Big Five" personality traits: extraversion, agreeableness, openness, conscientiousness, and neuroticism, as these profound aspects exert their influence on thoughts, emotions, and behaviors. The research passionately underscores the profound relevance of these traits and attitudes in prognosticating diverse life outcomes, encompassing triumphant vocational pursuits and overall well-being. Moreover, the study fearlessly embarks on an exploration of how these traits and attitudes intricately intertwine with the audacious world of entrepreneurship and the journey into self-employment. Additionally, the research passionately unravels gender disparities, unveiling evidence that males often display heightened assertiveness, aggression, and reduced anxiety when contrasted with their female counterparts. This invaluable understanding of the distinctions provides a cornucopia of insights, nurturing personal and professional growth, and beckoning forth a resolute, comprehensive, and all-inclusive approach to unraveling the enigmas of social and psychological research.
Keywords: Gender Differences; Personality Traits; Attitudes